The profession of elementary teaching from the perspective of school administrators - Turan, Mehmet; Turhan, Muhammed (My University, 2011)
The purpose of this study was to identify how school administrators perceive the elementary teaching profession and elementary teachers. The population of the study comprised the administrators of elementary schools located in the center of Elazi?, Adana and Malatya. A total of 185 questionnaires were sent to the school administrators included and they were included in the sample. Of these, 153 were returned and analyzed. According to views of school administrators; young teachers implement new instructional methods and techniques better, elementary teaching requires affection. Elementary teaching is not only a woman's profession, however, it is true that female teachers adapt to the profession less easily than their male colleagues, when compared to vice principals, more principals believe that elementary teaching is a difficult branch. © 2011 Academic Journals.
Keywords: Elementary teaching; Perspective of school administrators; Profession of elementary teaching